Correlation Between Tp-Te Interval With the Degree of Disfunction in Liver Cirrhosis Based on Child Pugh Turcotte Score in Dr. Sardjito General Hospital - RA Aditya Adhi Puruhita; Hasanah Mumpuni; Neneng Ratnasari (Faculty of Medicine Universitas Gadjah Mada, 2020)
Background. Hyperdynamic syndrome due to portal hypertension in cirrhosis of the liver leads to failure ofcontractions and cardiac structures that result in complications of cardiomyopathy cirrhosis. The incidenceof arrhythmias was reported in various non- cardiac diseases including liver cirrhosis. We aim to evaluatethe T peak wave - T end (Tp-Te) as a parameter for suspected arrhythmias that occur in liver cirrhosis.Aims. To determine the correlation between the Tp-Te interval with dysfunction in the degree of livercirrhosis, which was assessed using the Child Pugh Turcotte score.Methods. This research is a cross-sectional study. Data taken from liver cirrhosis patients who has been metthe inclusion and exclusion criteria were admitted to the Inpatient and Outpatient Hospital Dr. Sardjito untilMay 2020, an assessment of the degree of dysfunction of liver cirrhosis with Child Pugh score Turcotte, andelectrocardiographic examination to assess Tp-Te wave. The independent variable was the Child Pugh Turcottescore, the dependent variable was the Tp-Te wavelength. Analysis of correlation data using the Spearman test.Results. Subjects included 51 patients with liver cirrhosis, correlation analysis found a strong correlation,the higher the Child Pugh Turcotte score was linearly correlated with the Tp-Te wavelength (r = 0.692; p<0.05). Wavelength Tp-Te at Child Pugh to any group showed a significant (p <0.001) , the wavelengthof Tp-Te Child Pugh A group 67.94 ± 7.80 ms, the Child Pugh B group 77.26 ± 8.38 ms, whereas inthe Child Pugh C group 92.31 ± 11.36 ms.Conclusion. There was a strong positive correlation between the Tp-Te interval with the degree of livercirrhosis dysfunction which was assessed using the Child Pugh Turcotte score.